Third‐trimester growth diversity in small fetuses classified as appropriate‐for‐gestational age or small‐for‐gestational age at birth. (1st December 2021) - Deter, R. L.; Lee, W.; Dicker, P.; Tully, E. C.; Cody, F.; Malone, F. D.; Flood, K. M.
ABSTRACT: Objective: We have shown previously that third‐trimester growth in small fetuses (estimated fetal weight (EFW) < 10 th percentile) with birth weight (BW) < 10 th percentile is heterogeneous using individualized growth assessment (IGA). We aimed to test our hypothesis that individual growth patterns in small fetuses with BW > 10 th percentile are also variable but in different ways. Methods: This was a study of 191 cases with EFW < 10 th percentile and BW > 10 th percentile (appropriate‐for‐gestational‐age (AGA) cohort), derived from the PORTO study. Composite size parameters were used to quantify growth pathology at individual third‐trimester timepoints (individual composite prenatal growth assessment score (−icPGAS)). The fetal growth pathology score 1 (−FGPS1), calculated cumulatively from serial −icPGAS values, was used to characterize third‐trimester growth patterns. Vascular‐system evaluation included umbilical artery (UA) and middle cerebral artery (MCA) Doppler velocimetry. Outcome variables were birth age (preterm/term delivery) and BW (expressed as growth potential realization index for weight (GPRIWT ) and percentile). The findings from the AGA cohort were compared with those from small fetuses (EFW < 10 th percentile) with BW < 10 th percentile (small‐for‐gestational‐age (SGA) cohort). Results: The AGA cohort was found to have 134 fetuses (70%) with normal growth pattern and 57 (30%) with growth restriction based on IGA criteria. Seven growth‐restriction −FGPS1 patterns were observed, including the previously defined progressive, late, adaptive and recovering types. The recovering type was the most common growth pattern in the AGA cohort (50.9%). About one‐third of fetuses without any evidence of growth restriction had significant unexplained abnormalities in the UA (34%) and MCA (31%) and elevated mean GPRIWT values (113 ± 12.5%). Comparison of the AGA and SGA cohorts indicated a significant difference in the distribution of −FGPS1 growth patterns ( P = 0.0001). Compared with the SGA cohort, the AGA cohort had more fetuses with a normal growth pattern (70% vs 38%) and fewer cases with growth restriction (30% vs 62%). While the recovering type was the most common growth‐restriction pattern in the AGA cohort (51%), the progressive type was the primary growth‐restriction pattern in the SGA cohort (44%). No difference in the incidence of MCA or UA abnormality was found between the SGA and AGA cohorts when comparing subgroups of more than 10 fetuses. Conclusions: Both normal‐growth and growth‐restriction patterns were observed in the AGA cohort using IGA, as seen previously in the SGA cohort. The seven types of growth restriction defined in the SGA cohort were also identified in AGA cases, but their distribution was significantly different. In one‐third of cases without evidence of growth pathology in the AGA cohort, Doppler abnormalities in the UA and MCA were seen. This heterogeneity underscores the difficulty of accurate classification of fetal and neonatal growth status using conventional population‐based methods. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.